Conference report: Trends, new technologies and implications for dementia diagnostics, treatment and care in Switzerland (Swiss Medical Weekly, 2025)
Dementia diseases represent a major burden for the directly affected people, their relatives and modern society. Despite considerable efforts in recent years, early and accurate disease diagnosis and monitoring is still a challenge while no cure is available in most cases. New drugs, in particular disease-modifying therapies, and recent technological advancements offer promising perspectives. The integration of novel biomarkers, artificial intelligence and digital health tools has the potential to transform dementia care, making it more personalised, efficient and adapted to the living conditions and needs of older people. In November 2023, the 7th Dementia Summit convened a panel of experts from geriatrics, neurology, neuropsychology, psychiatry, ethics as well as general medicine to discuss interdisciplinary challenges, advancements and their implications for the future of dementia care in Switzerland. The conference underscored the importance of a multidisciplinary approach to successfully integrate new technologies in both clinical-translational research and dementia prevention, diagnosis and care. While recent innovations represent major steps forward, their implementation also comes with important challenges including questions on healthcare system preparedness and adaptation, ethical aspects, technology literacy, acceptance and appropriate use.